2009
DOI: 10.1177/0095798409333585
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Discrimination and Black-White Health Disparities in Medical Care

Abstract: The current study of Black patients focuses on how discrimination contributes to racial disparities in health. The authors used a longitudinal methodology to study how perceived past discrimination affects reactions to medical interactions and adherence to physician recommendations. In addition, they explored whether these reactions and/or adherence mediate the relationship between discrimination and patients’ health. The participants in this study were 156 Black patients of low socioeconomic status at a prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 52 publications
4
94
1
Order By: Relevance
“…Patients completed questionnaires before their visit with a doctor on their health and adherence to treatments, and 4 and 16 weeks after the visit patients reported their adherence to physician recommendations and overall health. 2 The results revealed that perceived discrimination within doctor-patient relationships was significantly and negatively associated with patient wellbeing, reactions to the physician and adherence. 2 Additionally, 63% of Blacks in a study with Bird and Bogart in 2001 perceived discrimination in their interactions with their health care provider.…”
Section: Racial Health Disparitiesmentioning
confidence: 95%
See 3 more Smart Citations
“…Patients completed questionnaires before their visit with a doctor on their health and adherence to treatments, and 4 and 16 weeks after the visit patients reported their adherence to physician recommendations and overall health. 2 The results revealed that perceived discrimination within doctor-patient relationships was significantly and negatively associated with patient wellbeing, reactions to the physician and adherence. 2 Additionally, 63% of Blacks in a study with Bird and Bogart in 2001 perceived discrimination in their interactions with their health care provider.…”
Section: Racial Health Disparitiesmentioning
confidence: 95%
“…2 The results revealed that perceived discrimination within doctor-patient relationships was significantly and negatively associated with patient wellbeing, reactions to the physician and adherence. 2 Additionally, 63% of Blacks in a study with Bird and Bogart in 2001 perceived discrimination in their interactions with their health care provider. 2 The mistrust that Black populations have with physicians lead to later screenings for medical conditions, less frequent checkups, and overall poor health such as obesity and diabetes, and the development of behaviours such as smoking.…”
Section: Racial Health Disparitiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Finally, we investigate the consequences of the level of correspondence between implicit and explicit attitudes on employee well-being. While there has been very little work done on the relationships between implicit and explicit attitudes (Penner et al, 2009) and their consequences for how individuals feel and behave, it stands to reason that a divergence between implicit and explicit attitudes might have important, long-term effects on employee wellbeing. It is important to note that because implicit attitudes frequently operate outside of conscious awareness, cognitive dissonance is not necessarily triggered when they fail to correspond with their explicit counterparts.…”
Section: Hypothesismentioning
confidence: 99%